If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -2 + -3x = 6 Reorder the terms: -2 + 7x + -3x = 6 Combine like terms: 7x + -3x = 4x -2 + 4x = 6 Solving -2 + 4x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 4x = 6 + 2 Combine like terms: -2 + 2 = 0 0 + 4x = 6 + 2 4x = 6 + 2 Combine like terms: 6 + 2 = 8 4x = 8 Divide each side by '4'. x = 2 Simplifying x = 2
| -[4z-(13z+5)]=5+(8z+3) | | (x^2+16)(x^2-6x+9)=0 | | -4a(a+6)=12 | | 7t+22=2 | | 1.3=3d+0.7 | | 7c+15=9c+40 | | 3xsquared-18x+27=125 | | -9x^2-18x+12=0 | | 5(z+9)-8=-19 | | 440-4= | | -1x+110=258 | | 2x(x+3)=13x-3 | | 2x^2+8x+16=31 | | (x-(1-3i))(x-(1+3i))= | | 0=8-x^3 | | 3.5x+30-3x=34 | | x^2+28x+35=0 | | 3.5x+30-3x=345 | | t=6s+15.39 | | 2((3x-1)+2x)=10+(x+4)+(4x-1) | | 16-12=4w+2w-2 | | 3x^2+12x+k=0 | | 16=7+3*p | | -6(k-8)=-30 | | 3y-12x=9 | | 3/4k-2=3 | | -4=-9+n/4 | | 0.75k-2=3 | | 7.36-1.9(5.6)=x | | -2=a+1/11 | | 18-3.8(5.6)=x | | -.5x+4=3 |